Glycosylated piericidins from an endophytic streptomyces with cytotoxicity and antimicrobial activity. (July 2018) - Shang, Ning-Ning; Zhang, Zhouxin; Huang, Jian-Ping; Wang, Li; Luo, Jianying; Yang, Jing; Peng, Teng; Yan, Yijun; Ma, Ya-Tuan; Huang, Sheng-Xiong
Abstract Two new glycosylated piericidins, glucopiericidinol A3 (1 ) and 7-demethyl-glucopiericidin A (2 ), along with four known analogs were isolated from the culture broth ofStreptomyces sp. KIB-H1083. The chemical structures of new compounds were elucidated by spectroscopic analyses. Their cytotoxicity on HL-60, SMMC-772, A-549, MCF-7, and SW480 cell lines, as well as antimicrobial activities was evaluated. The results showed that glucopiericidin A (4 ) has potent cytotoxicity against HL-60, SMMC-772, A-549, and MCF-7 cell lines with IC50 values of 0.34, 0.65, 0.60, and 0.50 μm, respectively. For the antimicrobial activity, piericidin A (6 ) showed most powerful inhibitory activities againstXanthomonas oryzae pv. oryzicola, andPenicillium decumbens .